Epidemiological Characteristics,Clinical Manifestation and Laboratory Finding of Pregnant Women with Chikungunya Infection in Trang Hospital - ชูคง สุธารัตน์; คูหะรัตน์ สุริยะ; ธรรมปาโล สุวิช (Disease Control Journal, 2011)
This study aimed to descript epidemiological characteristics, sign and symptoms and finding of laboratory examinations of the pregnant with Chikungunya infection. The data of in-patients pregnant women of Trang Hospital from January to December 2009 were reviewed. The results revealed that there were the pregnant with Chikungunya infection 148 cases. Only 116 cases were collected the data, of which was classified into 80 suspected cases and 36 confirmed cases (by RT -PCR). The average age was 26 years and most of them worked in rubber plantation (55.17%). The average gestational age was 31.29 weeks and most of them had the first time of pregnant. The fetal heart sound higher than 160 times/minutes was found 27 %. The sign and symptoms was fever (>38 ๐ c)(62.9.%), rash (92%) and arthritis (87.6%). The most of cases had number of leucocytes/mm3 5,000 - 10,000 (56.6%), number of platelets/mm3 > 100,000 (93.8%) and blood concentration < 34% (53.1%). This study showed that pregnant women were risk to be infected by Chikungunya because they worked in rubber plantation even they had gestational age in the 3 rd trimester. Their sign and symptoms of pregnant women with Chikungunya infection were similar to general people but terrible effects to fetus were considered. Therefore, the pregnant women were risk groups which should be carefully treated both before and during illness of Chikungunya